Complex interpretation of seismic data along the profile of the CMPV-GSN Sinelnikovo-Chuguev - D. V. Lysynchuk; E. V. Kolomiets; M. V. Kozlenko; Yu. V. Kozlenko; V. D. Omelchenko; L. T. Kalyuzhnaya (Геофизический журнал, 2013)
The complex interpretation of seismic data along DSS -CMRW profile Sinelnikovo - Chuguev was done. The crust along the profile has found a complex layered-block structure with differences throughout the depth of all section in three major structural elements: Ukrainian Shield, Dnieper-Donets depression (DDD) and the Voronezh Massif. Sedimentary cover is most powerful in the DDD. It consists of two structural floors: upper (divided into layers of low velocity) and homogenous lower with high seismic waves velocities. The earth crust consists of upper and lower parts. Those parts are different in reflective properties and velocity characteristics which are varying in depth and along the profile. The crust’s thickness is 33-40 km. The upper mantle reflections may be as-sociated with possible more ancient another Moho boundary. Major structural faults in the upper floor of DDD are laying the mantle and, consequently, can provide the channels for the flow of hydrocarbons from deep parts of the sedimentary cover. Axial part of the mantle diaper is shifted northward relative to the center of the basin, wich suggests preferential southwestern disclosure of the Dnieper-Donets avlakogene.